KERUSAKAN MEKANIS BUAH PEPAYA (Carica Papaya l.) DENGAN MENGGUNAKAN ALAT SIMULATOR MEJA GETAR - Elivia Salulinggi; Ireine A. Longdong; Stella M.E. Kairupan; Ruland A. Rantung (Universitas Sam Ratulangi, 2014)
ABSTRACTPapaya ( Carica papaya L ) is a fruit that comes from the tropical regions of the Americas that werethen distributed to various places by the Portuguese and Spanish, including India and other tropicalcountry. This research aims to study the mechanical failure vibration style fruit such as papaya, bruises,abrasions and scratches during transport of the simulation process. And to study the changes in color andhardness levels papaya fruit after 3 days of storage. The first phase of the research observes andmechanical damage by observing the appearance of the fruit papaya fruit surface abrasions and bruisesas a result of the transport simulation. after 3 days of storage of papaya fruit appearance began tomalfunction which can no longer be consumed by consumers. Papaya fruit texture changes beforesimulation on the green mature namely: 7.26 kg/cm2, the half-baked 4.5 kg/cm2, while the cook full 1.9kg/cm2. After 3 days of storage the texture of ripe green papaya decreased hardness is 4.26 kg/cm2, halfcook 2.33 kg/cm2 and 1.45 kg/cm2 fully ripe. Discoloration on papaya fruit increased after 3 days ofstorage, the green ripe 40.82 (+) half- ripe 48.37 (+) and fully ripe 57.89 (+). While vibration for 15minutes resulted in a full ripe papaya fruit suffered abrasions, bruises nearly all papaya fruit surface .Keywords : Papaya fruit, mechanical damage, the amount of vibration .